1991
DOI: 10.1128/jb.173.18.5631-5638.1991
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ompF porin expression by salicylate in Escherichia coli

Abstract: The expression of ompF, the gene encoding a major outer membrane protein of Escherichia coli, is regulated by various environmental factors. The mechanism by which salicylate (SAL) drastically reduces ompF expression was studied here by means of lacZ fusions to ompF, ompC, and micF, by sodium dodecyl sulfate-gel electrophoresis of outer membrane proteins, and by measurements of outer membrane permeability. Growth of E. coli in LB broth containing SAL strongly reduced ompF-specific translation of an ompF-lacZ f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
57
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 47 publications
(51 reference statements)
3
57
1
Order By: Relevance
“…Regulation of porin expression also occurs in response to chemicals in the environment. It was found in 1991 that salicylate in the medium decreased OmpF synthesis (560). This is now known to be a part of the global regulation of porins mediated by three XylS-AraC family regulatory proteins, MarA, SoxS, and Rob (9,174).…”
Section: Classical Porinsmentioning
confidence: 99%
“…Regulation of porin expression also occurs in response to chemicals in the environment. It was found in 1991 that salicylate in the medium decreased OmpF synthesis (560). This is now known to be a part of the global regulation of porins mediated by three XylS-AraC family regulatory proteins, MarA, SoxS, and Rob (9,174).…”
Section: Classical Porinsmentioning
confidence: 99%
“…We thus used cells in early stationary phase (36). With cefazolin, OmpF was further repressed by adding 5 mM sodium salicylate to the medium (37). Cells were grown at 30°C (except for cephaloridine) because this appeared to improve the expression of the TEM ␤-lactamase in strain HN1160.…”
Section: Determination Of Fluxes Of Cephalosporinsmentioning
confidence: 99%
“…Salicylate inhibits the binding of MarR to mar operator region of the mar operon which then leads to increased production of MarA and a decrease in antibiotic accumulation associated with a reduction in the production of the outer membrane porins OmpF and OmpC and to a concomitant increase in the production of the multidrug efflux pump AcrAB. 12,13 MarA expression is also involved in the virulence of E. coli. Using a murine model of pyelonephritis, Casaz et al 14 observed that strains lacking this gene were unable to maintain colonization of the kidney.…”
mentioning
confidence: 99%